Professional burnout - a comparative analysis considering the selected sectors in Poland = Wypalenie zawodowe - analiza porównawcza z uwzględnieniem głównych branż w Polsce - Witkowski, Stanisław; Ślazyk-Sobol, Magdalena (Zielona Góra: Faculty of Economics and Management Press)
The article presents the results of empirical research referring to the problem of burnout caused by professional burnout among staff of the most significant sectors in Poland. The authors presents the first part of the research project which also covered re-examination conducted after the interval of nine months. The research focused at the search for predictors of the phenomenon of burnout which - according to the latest concept of Maslach and Leiter - are as follows: emotional exhaustion, cynicism ad a reduced sense of personal achievements.
Keywords: wypalenie zawodowe; klimat organizacyjny; stres organizacyjny; professional burnout; organisational climate; organisational stress